Attitudes and Perceptions of Students to Open and Distance Learning in Nigeria - Ojo, David Olugbenga; Olakulehin, Felix Kayode (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2006)
In the West African Region of Africa, the National Open University of Nigeria (NOUN) is the first full fledged university that operates in an exclusively open and distance learning (ODL) mode of education. NOUN focuses mainly on open and distance teaching and learning system, and delivers its courses materials via print in conjunction with information and communication technology (ICT), when applicable. This 'single mode' of open education is different from the integration of distance learning system into the face- to- face teaching and learning system, which is more typical of conventional Universities in Nigeria and other parts of the world. Thus, NOUN reflects a novel development in the provision of higher education in Nigeria. This study assesses the attitudes and perceptions of distance teaching and learning by students enrolled in the NOUN and of the National Teachers' Institute (NTI) compared to their experiences at conventional universities. One hundred and twenty (n = 120) randomly selected NOUN and NTI students of NOUN were the subjects of the study. The Students' Attitude and Perception Rating of Open and Distance Learning Institutions Inventory (SAPRODLII), developed by the researchers, was administered to the subjects to measure their attitudes and experiences. Results of the study showed that students generally have a positive perception and attitude towards ODL, compared to traditional forms of higher education.